Mechanisms of laser energy absorption and melting behavior during selective laser melting of titanium-matrix composite: role of ceramic addition. (11th January 2021) - Ge, Qing; Gu, Dongdong; Dai, Donghua; Ma, Chenglong; Sun, Yixuan; Shi, Xinyu; Li, Yanze; Zhang, Hongmei; Chen, Hongyu
Abstract: The laser energy absorption and melting behavior of ceramic reinforced metal matrix composites during selective laser melting (SLM) additive manufacturing are vital for the subsequent metallurgical behavior. In this study, the mesoscopic simulation was proposed to investigate the influence of ceramic addition on the laser energy absorption and powder melting behaviors during SLM of TiC/Ti6Al4V composites. As the addition of TiC particles increased from 0 wt.% to 5 wt.%, the packing density of composite powder increased from 2.357 g cm −3 to 2.588 g cm −3, while the hall velocity decreased from 36.00 s to 73.14 s, indicating the powder flowability decreased with the ceramic addition. Meanwhile, the number of laser-powder interactions increased from 1.267 × 10 6 to 1.626 × 10 6, thereby enhancing the laser multiple reflection phenomenon in the powder bed. The concentrated irradiance distribution on the metal powder was dispersed into the surrounding powder. The average irradiance intensity on TiC particles was continuously improved, which increased the overall laser absorptivity from 0.655 to 0.72, yielding an elevated maximum operating temperature within the molten pool from 3501 K to 3668 K. However, with the excessive addition of ceramics (5 wt.%), balls and trapped unmelted particles deteriorated the surface morphology of the melted track. It can be attributed to the high required energy for complete melted TiC and the elevated difficulty of completely wetting unmelted particles. These results provided the physical understanding of high-quality and defect-free components of SLM processed composite materials.